Structural and electrochemical properties of NiCo2S4@N-doped graphene oxide/carboxy methyl cellulose interface composite for supercapacitor electrode materials. (25th November 2022) - Ramesh, Sivalingam; Karuppasamy, K.; Vikraman, Dhanasekaran; Yadav, H.M.; Kim, Hyun-Seok; Kim, Joo-Hyung; Kim, Heung Soo
Abstract: Recently, the graphene-carboxy methyl cellulose (GO-CMC) materials were fabricated as bio-medical, biosensors and supercapacitor applications. The fabrication of NiCo2 S4 @NGO and NiCo2 S4 @NGO/CMC composite electrodes was prepared via sonication assisted hydrothermal reaction for supercapacitor application. The as-prepared composite materials were described using FTIR, Raman, XRD, XPS, SEM, and SEM–EDX analysis. The composite results were confirmed structural, morphological, and surface properties to enhance the electrochemical properties for supercapacitor application. The resultant composite materials showed improved specific capacitance (493 and 767 F/g at 2 A/g), high-rate capability, and excellent cycling stability and capacity retention (5000 cycles with 95.1 %). Due to the surface and interfacial properties, the structural and morphological properties of NiCo2 S4 @NGO and NiCo2 S4 @NGO/CMC composite improved the specific capacitances and cyclic stability for supercapacitor application. The electrochemical properties were enhanced due to the interfacial properties of the NiCo2 S4 on NGO/CMC surface via sonication-assisted hydrothermal reaction process. Therefore, the composite materials demonstrated excellent electrochemical properties for potential supercapacitor application via 3 M KOH as electrolyte. Graphical abstract: Unlabelled Image Highlights: Synthesis of NiCo2 S4 on nitrogen doped graphene oxide/CMC composite by hydrothermal process. The construction of composite electrode for supercapacitor applications via three-electrode configuration The composite electrode exposed the excellent retention with improved specific capacitances. The fabricated electrode materials showed excellent cyclic stability on the 3M KOH electrolyte.